1957
DOI: 10.1021/ja01580a022
|View full text |Cite
|
Sign up to set email alerts
|

A Kinetic Study of the Ultraviolet Decomposition of Biochemical Derivatives of Nucleic Acid. I. Purines1

Abstract: Irradiation of Purines 6187 filtrates concentrated by vacuum distillation through a 14" column. The residue is subjected to vacuum distillation through a 5" column. The desired aminoalcohol distils as a viscous oil, b.p. 104-106°( 0.1 mm.), yield 56.3 g., (90.8%), re26D 1.5087. 4-Morpholino-2-butynyl N-Methylpipecolinate.-Into a 500-cc. 3-necked round bottom flask equipped with stirrer, reflux condenser, Dean-Stark water separator (CaCla tube) and heating mantle is placed a solution of 31.4 g. (0.20 mole) of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

1961
1961
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…We have found that the binding of deoxyinosine 3Ј-endonuclease to the DNA blocks the recognition of hypoxanthine by the AlkA protein, leading to a strong inhibition of the removal of hypoxanthine by AlkA protein. 1 Therefore, based on the current biochemical data, it is unlikely that AlkA protein will be able to remove deoxyinosine from DNA when deoxyinosine 3Ј-endonuclease is present. Binding to DNA, even after nicking, indicates that deoxyinosine 3Ј-endonuclease not only acts as an endonuclease but also as a DNA binding protein.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have found that the binding of deoxyinosine 3Ј-endonuclease to the DNA blocks the recognition of hypoxanthine by the AlkA protein, leading to a strong inhibition of the removal of hypoxanthine by AlkA protein. 1 Therefore, based on the current biochemical data, it is unlikely that AlkA protein will be able to remove deoxyinosine from DNA when deoxyinosine 3Ј-endonuclease is present. Binding to DNA, even after nicking, indicates that deoxyinosine 3Ј-endonuclease not only acts as an endonuclease but also as a DNA binding protein.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, no turnover of the enzyme cleavage activity was observed when duplex I/T or duplex I/C was used as a substrate. 1 However, deoxyinosine 3Ј-endonuclease retains nicking activity on duplex C and duplex D and exhibits a turning over of cleavage, since the enzyme cannot form stable complexes with these duplexes. One can speculate that other repair protein(s) brought to the damage site by interacting with deoxyinosine 3Ј-endonuclease in the protein-DNA complex would make an incision in the DNA 5Ј to deoxyinosine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Superoxide ions can react with the purine peroxyl radicals forming 'OH and purine alkoxyl radica1s.j' These radicals can react further with Ado resulting in an increase in its destruction yield relative to anacrobic conditions. The reactions of the hydroxyl radical with the purines substituted at C (6) and N(9) positions have also been studied by Steenken and Vieiraj8; these researchers reported that the unimolecular transformation reaction of the O H adduct formed when hydroxyl radicals attack Ado (Eq. 13) include the opening of the imidazole moiety and the -OH elimination (dehydration process) (Eqs.…”
Section: Dlscllssionmentioning
confidence: 99%
“…and adenylic acid to inosinic acid ( 5 ) . The ultraviolet irradiation of adenine solutions has been reported to give trace quantities of hypoxanthine ( 6 ) .…”
Section: Deamination Of Adenine By Ionizing Radiationmentioning
confidence: 99%